Cells of origin of ovarian cancer: ovarian surface epithelium or fallopian tube? - Klotz, Daniel Martin; Wimberger, Pauline (Archives of gynecology and obstetrics, 2017)
ObjectiveOvarian cancer is the fifth most common cancer in women and one of the leading causes of death from gynecological malignancies. Despite of its clinical importance, ovarian tumorigenesis is poorly understood and prognosis remains poor. This is particularly true for the most common type of ovarian cancer, high-grade serous ovarian cancer.ResultsTwo models are considered, whether it arises from the ovarian surface epithelium or from the fallopian tube. The first model is based on (1) the pro-inflammatory environment caused by ovulation events, (2) the expression pattern of ovarian inclusion cysts, and (3) biomarkers that are shared by the ovarian surface epithelium and malignant growth. The model suggesting a non-ovarian origin is based on (1) tubal precursor lesions, (2) genetic evidence of BRCA1/2 mutation carriers, and (3) recent animal studies. Neither model has clearly demonstrated superiority over the other. Therefore, one can speculate that high-grade serous ovarian cancer may arise from two different sites that undergo similar changes. Both tissues are derived from the same embryologic origin, which may explain how progenitor cells from different sites can respond similar to stimuli within the ovaries. However, distinct molecular drivers, such as BRCA deficiency, may still preferentially arise from one site of origin as precancerous mutations are frequently seen in the fallopian tube.ConclusionsConfirming the origin of ovarian cancer has important clinical implications when deciding on cancer risk-reducing prophylactic surgery. It will be important to identify key biomarker to uncover the sequence of ovarian tumorigenesis.